Puffy Hand Syndrome Revealed by a Severe Staphylococcal Skin Infection. (2nd October 2013) - Amode, Reyhan; Bilan, Paul; Sin, Carole; Marchal, Anaïs; Sigal, Michèle-Léa; Mahé, Emmanuel
Abstract : Puffy hand syndrome develops after long-term intravenous drug addiction. It is characterized by a nonpitting edema, affecting the dorsal side of fingers and hands with puffy aspect. Frequency and severity of the complications of this syndrome are rarely reported. Local infectious complications such as cellulitis can be severe and can enable the diagnosis. Herein, we report the case of a 41-year-old man who went to the emergency department for abdominal pain, fever, and bullous lesions of legs and arms with edema. Bacteriologic examination of a closed bullous lesion evidenced a methicillin sensitive Staphylococcus aureus . The abdomen computed tomography excluded deep infections and peritoneal effusion. The patient was successfully treated by intravenous oxacillin and clindamycin. He had a previous history of intravenous heroin addiction. We retained the diagnosis of puffy hand syndrome revealed by a severe staphylococcal infection with toxic involvement mimicking a four limbs cellulitis. Puffy hand syndrome, apart from the chronic lymphedema treatment, has no specific medication available. Prophylactic measures against skin infections are essential.